If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -4x = -3 + -2x Solving 1 + -4x = -3 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 1 + -4x + 2x = -3 + -2x + 2x Combine like terms: -4x + 2x = -2x 1 + -2x = -3 + -2x + 2x Combine like terms: -2x + 2x = 0 1 + -2x = -3 + 0 1 + -2x = -3 Add '-1' to each side of the equation. 1 + -1 + -2x = -3 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = -3 + -1 -2x = -3 + -1 Combine like terms: -3 + -1 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| x^2+12x+15=2x+6 | | (4x+9)(9x-4)=0 | | 9x-729=0 | | 3z-6z=5z-7+5z | | -5+Y=-2(X+3) | | x-6=17-4x | | 28*5x+2=21*7x | | 8x+20-x^2=0 | | 7x-3+5x=-7-8 | | 2(2x+1)=3x-7x | | 4(2k-5)=4 | | -2(x+3)+4=6(x+3)+8 | | 2x+3x-6=5+4 | | 3(7x+54)=-111 | | 6(3x+2)=72 | | 7x^2-14x-54=2 | | n+50=-12 | | x^2-5x=-7x+3 | | -4x-13=15 | | -6a+3=-9 | | 12=8x-3 | | 5r+7(2r+6)=8r-24 | | 6x-4(7-x)=15 | | -7a+3=17 | | 3x-6=5x+25 | | y^6*y^6=0 | | 3x+13=-23-3x | | 7(x+3)+2=3x+4(5+x) | | 4(x+1)=6x-2 | | 5a+3-2a=a | | 7x+1=3x-20 | | (5a-6)=(564*9) |